2003
DOI: 10.1191/0961203303lu444oa
|View full text |Cite
|
Sign up to set email alerts
|

Relapses of lupus nephritis: incidence, risk factors, serology and impact on outcome

Abstract: We prospectively followed a cohort of 46 newly diagnosed cases of lupus nephritis (LN) over a mean period of five years in order to determine the renal relapse rate, to identify potential risk factors for relapses, to assess the value of serological tests during flares and to analyse their impact on global outcome. Of the patients 37% experienced at least one renal flare, the first episode occurring after a mean follow-up of 40 months, when most patients were still treated with low-dose glucocorticoids and aza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
2
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 19 publications
5
48
2
6
Order By: Relevance
“…The choice of 9 mo may be too short a period for the full expression of the benefits, and this may thus bias the study to show benefits for a regimen that has a somewhat more rapid onset of action. Moreover, as studies have shown, 32,33 relapses of LN may be common after the induction treatment. A prolonged follow-up period is needed for the exploration of this treatment's impact on long-term prognosis and the recurrence rate during the maintenance therapy period.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of 9 mo may be too short a period for the full expression of the benefits, and this may thus bias the study to show benefits for a regimen that has a somewhat more rapid onset of action. Moreover, as studies have shown, 32,33 relapses of LN may be common after the induction treatment. A prolonged follow-up period is needed for the exploration of this treatment's impact on long-term prognosis and the recurrence rate during the maintenance therapy period.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of survival analysis, the cumulative relapse rate at 5 yr in our MMF-treated patients was approximately 40%. For comparison, we have reported that relapses occurred in 39% of patients on CTX-AZA treatment during 87 mo of follow-up (5), and other investigators have reported relapse rates of 41% over 4 yr or 37% over 5 yr in patients who were treated with CTX induction followed by AZA maintenance (26,27). In another study on patients who were treated with pulse cyclophosphamide, pulse methylprednisolone, or the combination of both, 45% of patients relapsed during 117 mo of follow-up (15).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Despite the successful induction of proliferative GN, relapses are common, ranging from 10 to 65%. [12,13] Continued renal damage can adversely affect long-term renal survival with each relapse, [14] and the treatment of these relapses is burdened by the toxicity. Consequently, optimal treatment and duration of maintenance therapy remains a challenge.…”
Section: G M Sahin Et Almentioning
confidence: 99%
“…[13] Although long-term cyclophosphamide (CY) regimens are efficacious in the treatment of proliferative lupus nephritis and has improved the prognosis of disease in these patients, the safety of the regimen still limits the success of therapy. There has been increasing attention on developing alternate therapies that promptly and effectively induce remission, prevent relapse, and maximize patient and renal survival while incurring the least toxicity.…”
Section: Introductionmentioning
confidence: 99%